2009
DOI: 10.4177/ccgp-d-09-00007.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Variables that Influence Mercury Capture in Solid Sorbents

Abstract: A B S T R A C TNewly obtained results on mercury retention in fly ashes and activated carbons during coal combustion are compared with previous findings. The influence of different variables on mercury capture, including the composition and nature of the sorbents, the composition of the flue gas and the mercury species in gas phase is investigated.Coal-fired utility boilers are currently the largest single-known source of mercury emissions. According to the USEPA's Information Collection Request (ICR), on aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Therefore, in addition to HgCl 2 , the presence of Hg 0 cannot be ruled out. (Table 1) are what one would expect in a gasification atmosphere containing H 2 S. In previous studies [19,34], it was suggested that the Hg species formed in the N 2 and gasification atmospheres were the same because the retention capacities in both atmospheres were similar. However, the results obtained from thermal desorption in this study show that, while Hg is present mainly as HgCl 2 in the N 2 atmosphere (Figure 3), in the gasification atmosphere it is in the form of HgS ( Figure 5).…”
Section: Analysis Of Mercury Species In Fly Ashes Post-retentionmentioning
confidence: 48%
See 3 more Smart Citations
“…Therefore, in addition to HgCl 2 , the presence of Hg 0 cannot be ruled out. (Table 1) are what one would expect in a gasification atmosphere containing H 2 S. In previous studies [19,34], it was suggested that the Hg species formed in the N 2 and gasification atmospheres were the same because the retention capacities in both atmospheres were similar. However, the results obtained from thermal desorption in this study show that, while Hg is present mainly as HgCl 2 in the N 2 atmosphere (Figure 3), in the gasification atmosphere it is in the form of HgS ( Figure 5).…”
Section: Analysis Of Mercury Species In Fly Ashes Post-retentionmentioning
confidence: 48%
“…The amount of Hg 0 captured in the gasification atmosphere and in N 2 was similar, the highest capture being achieved in the combustion atmosphere [19]. However, when the source of mercury was HgCl 2 , the retention was similar in all three atmospheres [34].…”
Section: Analysis Of Mercury Species In Fly Ashes Post-retentionmentioning
confidence: 75%
See 2 more Smart Citations
“…Several full-, pilot-, and bench-scale studies have revealed that fly ashes can both adsorb and oxidize Hg in coal combustion flue gases [6][7][8][9][10][11][12][13][14]. A number of investigations have attempted to correlate Hg retention and oxidation with the content and characteristics of unburned carbon in raw fly ashes [15][16][17] and have found that, in general, Hg capture increases in fly ashes with a high carbon content [18].…”
Section: Because the Different Modes Of Occurrence Of Hg Involve Diffmentioning
confidence: 99%